Out of the shadows : expanding the canon of classic film noir - Phillips, Gene D. (Scarecrow Press, Inc., 2012)
Film noir was a cycle in American cinema which first came into prominence during World War II, peaked in the 1950s, and began to taper off as a definable trend by 1960. Over the years, a group of films from the period emerged as noir standards, beginningwith Stranger on the Third Floor in 1940. However, since film noir is too wide-ranging, it cannot be kept within the narrow limits of the official canon that has been established by film historians. Consequently, several neglected movies made duringthe classic noir period need to be re-evaluated as noir films. In Out of the Shadows: Expanding.